2018
DOI: 10.1186/s13643-018-0778-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex/gender reporting and analysis in Campbell and Cochrane systematic reviews: a cross-sectional methods study

Abstract: BackgroundThe importance of sex and gender considerations in research is being increasingly recognized. Evidence indicates that sex and gender can influence intervention effectiveness. We assessed the extent to which sex/gender is reported and analyzed in Campbell and Cochrane systematic reviews.MethodsWe screened all the systematic reviews in the Campbell Library (n = 137) and a sample of systematic reviews from 2016 to 2017 in the Cochrane Library (n = 674). We documented the frequency of sex/gender terms us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 52 publications
6
17
1
Order By: Relevance
“…Only one in three studies reported inclusion of sex or gender in their study design. These results reflect parallel trends that have been observed in other clinical specialties such as surgery, radiology, and neurosciences and include prestigious journals and Cochrane reviews . While federal mandates have an important influence in ascertaining the direction of future research by inspiring researchers to reflect on the role of SGBM in their individual research, it does not necessarily translate into research practice.…”
Section: Discussionsupporting
confidence: 71%
“…Only one in three studies reported inclusion of sex or gender in their study design. These results reflect parallel trends that have been observed in other clinical specialties such as surgery, radiology, and neurosciences and include prestigious journals and Cochrane reviews . While federal mandates have an important influence in ascertaining the direction of future research by inspiring researchers to reflect on the role of SGBM in their individual research, it does not necessarily translate into research practice.…”
Section: Discussionsupporting
confidence: 71%
“…These findings are consistent with results from a study on Campbell and Cochrane systematic reviews [62]. Petkovic et al (2018) found that reporting in systematic reviews is inadequate [62]. None of the studies in our systematic review included gender diverse populations or other gender considerations.…”
Section: Discussionsupporting
confidence: 91%
“…Throughout the studies, authors used "male/female" and "women/men" and the use of "gender" was inaccurate. These findings are consistent with results from a study on Campbell and Cochrane systematic reviews [62]. Petkovic et al (2018) found that reporting in systematic reviews is inadequate [62].…”
Section: Discussionsupporting
confidence: 89%
“…Health systems can make important contributions to this SDG by tracking gender inequalities and addressing underlying structural issues, including gender-based assessments of approaches to budgeting [ 18 ]. While it is increasingly acknowledged that monitoring sex-specific impacts of health interventions is a critical starting point, sex and gender reporting remains inadequate in health research [ 19 , 20 ]. Petkovic et al’s study of recent systematic reviews documented that less than 30% of reviews reported on sex or gender in the results [ 20 ].…”
Section: Introductionmentioning
confidence: 99%